Practical tips to adopt active lifestyle for university students during pandemic life: a narrative review - Zaenal Muttaqien Sofro; Widya Wasityastuti; Rakhmat Ari Wibowo; Rahmaningsih Mara Sabirin; Siswanto Siswanto; Jajar Setiawan; Denny Agustiningsih (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2022)
The Covid-19 pandemic worsened the physical inactivity pandemic and also increased sedentary behavior across the population, including university students. While physical inactivity and sedentary behavior are detrimental to health and academic performance, there is an urgent need to help university students to adopt an active lifestyle during post-pandemic life. This narrative review discussed current physical activity (PA) and sedentary behavior recommendations, practical tips for adopting an active lifestyle by applying PA doses using the frequency, intensity, time, and type (FITT) principle, and behavioral strategies to adopt and maintain an active lifestyle. Finally, several considerations related to the PA-related musculoskeletal injury and cardiovascular events risks were also discussed with examples from interventions during the pandemic in university settings.